Atypical Lone Pair–π Interaction with Quinone Methides in a Series of Imido‐Ferrociphenol Anticancer Drug Candidates. Issue 25 (14th May 2019) - Wang, Yong; Pigeon, Pascal; Top, Siden; Sanz García, Juan; Troufflard, Claire; Ciofini, Ilaria; McGlinchey, Michael J.; Jaouen, Gérard
Abstract: Ferrociphenols, especially those possessing a heterocycle at the terminus of an aliphatic chain, display strong anticancer activity through a novel redox mechanism that generates active metabolites such as quinone methides (QMs). X‐ray crystallography and UV/Vis spectroscopy reveal that the specific lone pair (lp)–π interaction between a carbonyl group of the imide and the quinone motif of the QM plays an important role in the exceptional cytotoxic behaviour of their imido‐ferrociphenol precursors. This intramolecular lp–π interaction markedly enhanced the stability of the QMs and lowered the p K a values of the corresponding phenol/phenolate couples. As the first example of such a non‐covalent interaction that stabilizes QMs remotely, it not only expands the scope of the lp–π interaction in supramolecular chemistry, but also represents a new mode of stabilization of a QM. This unprecedented application of lp–π interactions in imido‐ferrociphenol anticancer drug candidates may also have great potential in drug discovery and organocatalyst design. Abstract : Heterocycle‐substituted ferrociphenols display strong anticancer activity through the generation of active metabolites such as quinone methides (QMs). The specific lone pair–π interaction between an imide carbonyl group and the quinone motif is crucial for the cytotoxic behaviour of their imido‐ferrociphenol precursors as it markedly enhances the stability of the QMs and lowers the p K a values of the corresponding phenolates.